Understanding urban food sharing landscapes: a role for assemblage thinking? - Davies, Anna; Cho, Hyunji (My University, 2025)
Urban food systems globally are unsustainable and in urgent need of reconfiguration. Research suggests that food sharing can form part of sustainability transitions at the urban scale. However, there has been limited interrogation by researchers of how individual food sharing initiatives (FSIs) interact and collaborate with others in places. Adopting a conceptual frame inspired by assemblage thinking, this paper identifies FSIs that operate within a district of inner-city Dublin, Ireland. Using mixed methods, we trace material, relational and financial flows between the FSIs active in the district and other actors and organisations. Drawing insights from this process, we conclude that locating and tracing food sharing relations productively identifies points of attachment as well as fractures and fragilities within FSI landscapes. This finding can be used by different stakeholders as a resource within the inherently political process of reshaping urban food systems towards more sustainable outcomes. However, further longitudinal research is required to identify the extent to which these emergent assemblages have the capacity to persist, expand and disrupt dominant patterns of power and influence within and beyond these webs of food sharing.
PUBLISHED
Keywords: Food system; assemblage; Dublin; Ireland; food sharing; health and well-being; Smart & Sustainable Planet; FOOD CONSUMPTION